GEMS-Pack: A Graphical User Interface for the Packmol Program - Silva, Lucas A; Correia, Julio C G (Journal of chemical information and modeling, 2020)
We present GEMS-Pack, a graphical user interface for Packmol. Since Packmol is largely used by the molecular simulation community, this work provides a complement to it, in the form of a user-friendly and efficient interface. A tool for number/volume/density calculation is provided to make needed calculations faster. Also, a visualization utility is included, which lets the users preview how their systems will look like even before running the packing procedure. This application does not modify the original Packmol code; it works in a complementary way, by generating the input script and running it through the system's terminal. This program is part of a development project and is intended to be further extended. Two examples are described in this paper to illustrate GEMS-Pack usage.